Revisiting ONE Simulator in IoV Research: Seeing the Forest Through the Trees - Hasan Mahmood Aminul Islam; Khalid Mahbub Khan; Mahamudur Rahman Maharaz; Angon Bhadra Antu; Farhad Billah; Shishir Majumder; Arham Khan (IEEE Access)
The Internet of Vehicles (IoV) refers to a large-scale distributed system that can be considered as the convergence of the mobile Internet and the Internet of Things (IoT). IoV represents an advanced evolution of vehicular communication networks, transitioning from the primary principles of Vehicular Ad hoc Network (VANET) to a more comprehensive framework that supports the dynamic interaction of vehicles, traffic management systems, and other elements of the environment. This dynamic interaction is referred to as V2X, where the X refers to vehicles, pedestrians, network elements, etc. The IoV ecosystem, in general, is very complex due to the diverse entities in the network. In this article, the complexities of IoV simulation are analyzed through the metaphorical lens of a tree to make sense of IoV ecosystems as hierarchical and interdependent structures. The metaphor “seeing the forest through the trees” reflects the existing IoV framework and the taking of a holistic approach that addresses the complexities of the IoV simulation using different relevant KPIs as well as can inspire a set of principles that shape the simulation of the IoV ecosystem through the ONE simulator. However, during the last two decades or more, many researchers and automakers have dedicated their efforts to developing tools for the experimentation, verification, and validation of IoV protocols and their applications. This study introduces the Opportunistic Network Environment (ONE) simulator as a suitable tool in IoV research. In addition, we have argued that the modular structure of the ONE simulator opens up a great landscape for students/researchers interested in researching IoV.